(untitled) (Research, Society and Development, 2024)
Exclusive Breastfeeding – EBF, when the child in the first six months of life, only has breast milk as a source of nutrition, whether this milk is introduced directly from the breast or expressed, without having to add any liquid or solid substance as a nutritional complement. Breastfeeding promotes immune protection for the child such as antibodies, enzymes and white blood cells, and breast milk has nutritional properties capable of nitriating the baby without. Objective: To describe the role of nursing professionals as advisors and promoters of breastfeeding practices in primary care. Methodology: the study presents a descriptive Narrative Literature Review. Data were collected from the database of the Journal of Research, Society and Development – RSD, Scielo and VHL. Results: analysis of the selection of publications, categorized the studies in chart 1, with identification of the topics number, author and date, title of the publication and the objectives of the studies. The results were 15 publications on consultation in the database. Final considerations: the health professional is the key player to guide the mother in the breastfeeding process, with support for the difficulties that may be generated in this new phase through strategies of effective approaches and interventions in nursing consultations.